2013
DOI: 10.2981/12-045
|View full text |Cite
|
Sign up to set email alerts
|

A presence‐only habitat suitability model for Persian leopard Panthera pardus saxicolor in Golestan National Park, Iran

Abstract: Top predators such as leopard Panthera spp. are often associated with high biodiversity, so the protection of their habitats is one of the most effective ways to conserve biodiversity globally. In this paper, we use ecological niche factor analysis (ENFA), a presence-only environmental habitat-envelope based method to create habitat suitability maps for Persian leopard in Golestan National Park (GNP), Iran. The Persian leopard Panthera pardus saxicolor is an endangered subspecies on the IUCN Red List of Threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…In contrast, other species, such as cheetah, more strongly avoid areas near human settlements. These results are consistent with the previously reported data on carnivore species (Erfanian et al., ; Omidi, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In contrast, other species, such as cheetah, more strongly avoid areas near human settlements. These results are consistent with the previously reported data on carnivore species (Erfanian et al., ; Omidi, ).…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with the previously reported data on carnivore species (Erfanian et al, 2013;Omidi, 2008).…”
Section: Influence Of Ecogeographical Variables On Species Potentiasupporting
confidence: 94%
See 1 more Smart Citation
“…Their taxonomy as a distinct subspecies still remains obscure until further evaluations, but for the time being this subspecies is traditionally assigned to P. p. saxicolor (Yusefi, Faizolahi, Darvish, Safi, & Brito, 2019), as some studies investigating craniological patterns and molecular genetics showed that Iran is inhabited only by P. p. saxicolor (Farhadinia et al, 2015). According to unsubstantiated estimates, between 550 and 850 leopards are distributed within about 6,050 km 2 in Iran, specifically in two great mountain ranges, the Zagros Mountains in the west and the Alborz Mountains in the north, which makes Iran the main stronghold of the leopard (Erfanian, Mirkarimi, Mahini, & Rezaei, 2013;Sharbafi, Farhadinia, Rezaie, & Braczkowski, 2016;Yusefi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Gradually reducing toward the east, the elevation ranges from 450 to 2,400 m above sea level. The mean annual precipitation is 150 in east and 700 mm in the west part [31] [32] [34]. The vegetation can be divided into two zones: the Hyrcanian forest in the west with a high humidity and the Iran-Turanian vegetation in the east of the park where it is dry [35].…”
Section: Study Areamentioning
confidence: 99%